Qualidade de vida e bem-estar psicológico entre gestantes de risco habitual acompanhadas nas unidades básicas de saúde do município de mossoró/rn. - Justino, Jéssica Micaele Rebouças (Universidade Federal Rural do Semi-Árido, 2019)
This is a descriptive, cross-sectional study with a quantitative approach that allowed us to investigate the association between quality of life and psychological well-being in pregnant women, considering its potentialities, with a view to enabling the reorientation of care during the pregnancy cycle, acting directly. in your needs and investing in your ability and control over your life. The research was conducted in the Basic Health Units located in the urban area of Mossoró / RN with 135 pregnant women at usual risk in prenatal care. Data were obtained through the application of three instruments: Socioeconomic Questionnaire and Clinical-Obstetric History, Ferrans & Powers Quality of Life Index (QLI) and Psychological Well-being Scale (PWS), after approval by the Ethics and Research Committee. under Opinion No. 2.893.813 CAAE: 96006518.0.0000.5294 and statistical analysis of the data was performed using the JASP version 0.10.2 program. Considering the information obtained from the analysis, it is inferred about the sociodemographic and clinical-obstetric profile, that there was a predominance of pregnant women with secondary education, mulattos, who do not work or take care of the home, Protestants, have income between 1 and 3 salaries, were in the 3rd trimester of pregnancy, first born, 1 to 3 deliveries and have no pathological history. Regarding the relationship between socioeconomic and clinical-obstetric variables with the QLI and PWS dimensions, it was found that there are statistical differences in some situations and all variables showed one to three relationships with some QLI and PWS dimensions, and these relationships occurred more in relation to quality of life. From the association established between quality of life and psychological well-being, it was seen that there is a strong relationship of complementarity between these constructs, when worked from the perspective of pregnant women at usual risk in the municipality in question. Given this, it is understood that conducting a study on the assessment of quality of life and psychological well-being of pregnant women is relevant to assist in directing and reorienting prevention, promotion and health care actions, with a view to improving practices currently performed in the public health network, improving the care offered to this population
Keywords: Gravidez; Qualidade de vida; Bem-estar psicológico; Atenção básica; Pregnancy; Quality of life; Psychological well-being; Basic attention; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES